Microstructure and functional properties of light weight AlMgxTiSnZn high entropy alloy - Satya Prasad Maddula; Venkata Swamy Naidu Neigapula; Balaji Rao Ravuri (Chemical Physics Impact)
Lightweight high-entropy alloys (LWHEAs) present new opportunities for exploring innovative, low-cost materials with a high strength-to-weight ratio, thanks to their expansive alloy-design space. This study introduces the newly designed AlMgxTiSnZn HEAs to examine the relationship between microstructure, phase stability, and functional properties (including mechanical, thermal, and electrochemical properties alongside oxidation resistance). These alloys were produced by mechanically mixing them in a high-energy ball mill (HEBM), followed by heating with spark plasma sintering (SPS). Thermodynamic calculations were utilized to ascertain the phase structure. XRD studies revealed a predominant ordered BCC phase with minor peaks indicating a tetragonal structure. The correlation between microhardness (Hv) and fracture strength (σf) with Mg content indicates that the HEA sample featuring the highest microhardness concurrently exhibits the highest fracture strength (AlMgTiSnZn). This AlMgTiSnZn HEA sample, noted for its high corrosion resistance and distinct properties (such as favorable over-potential, low corrosion current density (Icorr), and minimal corrosion rate), is particularly promising for high-temperature applications.